2016
DOI: 10.15406/unoaj.2016.03.00096
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Therapeutic Plasma Exchange; One Year Single Center Experience

Abstract: Background: Outcome of therapeutic plasma exchange (TPE) in treating different immunological and non-immunological diseases in our unit is not clear. We aimed to study the outcome TPE in different diseases categories during one-year period.Methods: Prospective cross sectional study of patients referred for TPE during one year period. Demographic, clinical data, number of sessions, volume of plasma exchanged, patient tolerance and complications during or post to the procedure were systematically recorded and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Myasthenia Gravis (MG) is an autoimmune disease characterized by presence of antibodies that attacking postsynaptic nicotinic acetylcholine receptors and presented with fluctuating weakness that may progress to life-threatening complications [20] . The study included 4 cases with myasthenia gravis that showed marvelous response after starting TPE (100% remission rate).…”
Section: Discussionmentioning
confidence: 99%
“…Myasthenia Gravis (MG) is an autoimmune disease characterized by presence of antibodies that attacking postsynaptic nicotinic acetylcholine receptors and presented with fluctuating weakness that may progress to life-threatening complications [20] . The study included 4 cases with myasthenia gravis that showed marvelous response after starting TPE (100% remission rate).…”
Section: Discussionmentioning
confidence: 99%
“…Ghonemy TA and colleagues [9] noted that therapeutic plasmapheresis is almost safe and effective adjuvant treatment for several diseases especially autoimmune diseases, like MG. Plasmapheresis achieved immediate improvement of MG symptoms, and, while it made patients attentive to the course of their disease, it also helped them realize that there was a possibility of relief.…”
Section: Introductionmentioning
confidence: 99%